ANALISIS BIAYA TRANSAKSI PADA INDUSTRI BANK UMUM DI INDONESIA - Listiyanto, Eko; Manzilati, Asfi (Journal of Indonesian Applied Economics, 2007)
The objectives of the research were to examine if there is difference in transactioncosts of Â loan transaction in comercial bank between the period befor the economiccrisis in 1997 and the period after, and to identify variables influencing the costs oftransaction. It was foung that there was a significant difference between both periodsmentioned. Variables affecting the transaction costs were Â overhead costs, and writeoff.Keywords: Transaction Cost, Adverse Selection, Moral Hazard, Ex Post Costs